The influence of relativism on the understanding of the human species in relation to social and technoscientific research as a bioethical problem - Contreras-Calderón, Joan (2024)
Postmodernity has been characterized by the constant use of relativism to be able to modify and re-signify every concrete and objective concept that is related to the human species. The identity crisis through the adoption of ideologies, materialism, the loss of deontological sense and human dignity are symbiotically related to the cultural, philosophical, social and techno-scientific problem that brings with it the relativization of concepts that are analyzed in the social research today and impact the bioethical understanding of human beings. Understanding the postmodern subject and the relativism that permeates it allows the philosopher, the anthropologist, the bioethicist, the political scientist, the sociologist, the psychologist, among others, to consider as a factor the problem that a relativist perspective raises in a materialist, individualist context and reification of the human species in the different areas of social research. Not all relativism is harmful, but there is one in particular that attracts the masses of postmodern subjects and that concerns a greater ideological, deontological and social crisis today: Second-Order Relativism as a bioethical problem.